A Novel Model for Simultaneous Evaluation of Hyperoxia-Mediated Brain and Lung Injury in Neonatal Rats - Stefanie Obst; Meray Serdar; Josephine Herz; Karina Kempe; Meriem Assili; Mandana Rizazad; Dharmesh Hirani; Miguel A. Alejandre Alcazar; Stefanie Endesfelder; Marius A. Möbius; Mario Rüdiger; Ursula Felderhoff-Müser; et al. (Cells)
Despite improved neonatal intensive care, the risk of premature-born infants developing bronchopulmonary dysplasia (BPD) and encephalopathy of prematurity (EoP) remains high. With hyperoxia being a major underlying factor, both preterm-birth-related complications are suggested to be closely interrelated. However, experimental models are lacking for the assessment of the potentially close interplay between both organs. To establish a model, suitable for the assessment of both affected organs, Wistar rats were exposed to 80% oxygen from postnatal day 2 (P2) for seven days. Brain and lung tissues were analysed via histomorphometry, immunohistochemistry, real-time PCR, and western blot at term P11. In the brain, hyperoxia induced significant hypomyelination accompanied by a reduction in oligodendrocytes and CD68 expression on microglia cells. These changes correlate with arrested alveolarisation and an increased number of macrophages in the lung. Interestingly, in contrast to the reduced formation of pulmonary microvessels, an increased vascular density was detected in the brain. Seven days of hyperoxia induces typical characteristics of BPD and EoP in neonatal rats, thereby linking impaired alveolarisation with disturbed myelination in the brain and providing an experimental model for understanding pathophysiological mechanisms and identifying organ-spanning novel therapeutic interventions targeting both diseases.